The Role of Border Cooperation of Kazakhstan with the EAEU Countries in the Economic Development of Cross-border Regions (Journal of Economic Research & Business Administration, 2018)
Border regions of Kazakhstan are elements of the national economy, which are constantly experiencing the direct and active influence of the integration processes in the conditions of the Eurasian Union. Cross-border international cooperation in trade, environment, agriculture, transport, security and communications takes place across border regions. In this regard, the purpose of this article is identification of features of border cooperation of Kazakhstan with the EAEU countries (on the example of Kazakhstan and Russia) and definition of its role in economic development of border regions. During the research have been studied foreign and domestic literature on a subject; the methods which are earlier used inresearches of the Russian scientists have been applied: such as calculation of the index of gravitation ofregions, the analysis of availability of transport and logistic networks and the special economic zones(SEZ) in border areas for assessment of potential for border cooperation of regions of two states. Based onthe results of the research, a SWOT analysis was compiled, which allows describing the role of border cooperationbetween Kazakhstan and Russia in the economic development of border regions of the country.According to the results of the analysis, border cooperation provides the following opportunities forthe economic development of the northern regions of the country: the revival of interrupted productionand industrial relations; development of cross-border infrastructure; development of tourism; the entryof regional producers into the international market; the replenishment of the labor market with qualifiedpersonnel and others. Risks: the threat to remain a source of raw for the Russian regions; demand reductionfor local products; the outflow of labor abroad, especially highly qualified specialists; increasingimbalances in cross-border trade.